(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda is not only the science of healing, but also the one which tells about the art of living. Well being of Shareera, Indriya, Satwa and Athma is necessary to achieve a long healthy life. Achara Rasayana is a unique concept told by Acharya Charaka which stresses upon various factors which are responsible for the well being of all these entities. The factors mentioned can be categorized as psychological, socio-behavioural, spiritual, food and life style aspects. All these aspects will have positive effects on the physical as well as the mental health, just like the Rasayana which helps in attaining longevity. Achara Rasayana is the need of the hour as most of the people are prone to psychosomatic illnesses due to the changed life style and stressful work schedules. An attempt is made to analyse the mode of impact of Achara Rasayana, along with the outcomes of various researches which scientifically substantiate the concept.